1999
DOI: 10.1046/j.1523-1747.1999.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Ceramide Subfractions Detectable in Cer(AS) Position by HPTLC in Skin Surface Lipids of Non-Lesional Skin of Atopic Eczema

Abstract: The non-involved skin of atopic eczema (NEAE) is characterized by severe dryness and an impaired barrier function of the stratum corneum as indicated by an increased transepidermal water loss. Previous studies have demonstrated that this barrier impairment coincides with marked alterations in the amount and composition of stratum corneum ceramides. The aim of this study was to identify specific alterations in NEAE that may be used in the diagnosis of the atopic eczema. Using a classical procedure for high perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
102
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 33 publications
6
102
0
Order By: Relevance
“…Keratinocyte-specific (K5-Cre) disruption of Hif1α led to no overt phenotype (S. Tomita et al, unpublished observations), suggesting that the HIF1α/ARNT heterodimer is not responsible for the phenotype observed in this study. Although SIM1 and SIM2 are other candidates that can form heterodimers with ARNT (46) and can possibly activate the desaturase gene in the epidermis (47), they analysis indicated that Cer(EOS) and Cer(NP) levels were significantly diminished in these skin diseases (40). It would be of interest to compare the detailed structures of lamellae of these patients and of Arnt-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte-specific (K5-Cre) disruption of Hif1α led to no overt phenotype (S. Tomita et al, unpublished observations), suggesting that the HIF1α/ARNT heterodimer is not responsible for the phenotype observed in this study. Although SIM1 and SIM2 are other candidates that can form heterodimers with ARNT (46) and can possibly activate the desaturase gene in the epidermis (47), they analysis indicated that Cer(EOS) and Cer(NP) levels were significantly diminished in these skin diseases (40). It would be of interest to compare the detailed structures of lamellae of these patients and of Arnt-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported signifi cant changes in CER subclasses in nonlesional SC of AE patients: reduced CER [NP], increased CER [AS], and reduced long chain CERs [EOH] and [EOS] ( 12,23,(34)(35)(36). Some of these changes could be correlated with changes in skin barrier function.…”
mentioning
confidence: 99%
“…Indeed, a deficiency in the synthesis of ULCFA-containing Cers results in the severe cutaneous disorder ichthyosis in both mice and humans (5)(6)(7)(8)(9)(10)(11). Furthermore, decreased levels of Cers and changes in Cer subclasses have been observed in the epidermis of persons with atopic dermatitis or psoriasis (12)(13)(14)(15)(16). Recently, shifts of Cers toward shorter chain lengths have also been reported in patients with atopic eczema (17).…”
mentioning
confidence: 99%